Accreditation as a Strategic Enabler for Patient Safety and Organizational Excellence: A Systematic Review - Rani, K Sandhya (Digital Repository of Theses, 2026)
Background Healthcare accreditation has evolved from a regulatory compliance mechanism to a potential strategic enabler for patient safety and organizational excellence. While numerous studies demonstrate that accreditation fosters improvements in safety outcomes, the evidence regarding its long-term effectiveness, sustainability, and integration with modern management frameworks remains fragmented and inconsistent across diverse healthcare contexts, particularly in low- and middle-income countries (LMICs). Objectives This systematic review aimed to: (1) synthesize evidence on accreditation's impact on patient safety outcomes including reductions in medical errors, hospital-acquired infections, and mortality; (2) explore how accreditation influences hospital policies, clinical practices, and staff adherence to safety protocols; (3) identify organizational changes, leadership engagement patterns, and culture transformation driven byaccreditation; (4) examine operational, financial, and contextual barriers to effective implementation, especially in LMICs; (5) assess the sustainability of improvements beyond initial certification cycles; and (6) compare the effectiveness of different accreditation models in alignment with strategic healthcare management. Methods This systematic review aimed to: (1) synthesize evidence on accreditation's impact on patient safety outcomes including reductions in medical errors, hospital-acquired infections, and mortality; (2) explore how accreditation influences hospital policies, clinical practices, and staff adherence to safety protocols; (3) identify organizational changes, leadership engagement patterns, and culture transformation driven by accreditation; (4) examine operational, financial, and contextual barriers to effective implementation, especially in LMICs; (5) assess the sustainability of improvements beyond initial certification cycles; and (6) compare the effectiveness of different accreditation models in alignment with strategic healthcare management. Results Of 37 included studies, six were rated high quality, 27 moderate quality, and four lower/unclear quality. Fifty-seven percent (n=21) of studies reported positive associations between accreditation and improved patient safety outcomes, 32% (n=12) reported mixed results, and 11% (n=4) showed no clear benefit. Meta-analytic synthesis for infection rates revealed a 22% lower risk in accredited hospitals (RR 0.78, 95% CI 0.64 to 0.94, p<0.01). Accreditation was associated with improved policy standardization (67% of studies), increased staff adherence to safety protocols (70% of studies), enhanced leadership engagement (65% of studies), and stronger safety culture scores (62% of studies). However, significant barriers emerged, particularly in LMICs: financial constraints (reported in 78% of LMIC-focused studies), inadequate infrastructure (73%), and insufficient trained personnel (69%). Sustainability of improvements varied considerably. Longitudinal data (8 studies) showed sustained benefits in 50% of cases over 2 to 3 years when continuous leadership support and monitoring were maintained, while 50% experienced deterioration within 12 to 18 months post-certification. Joint Commission International (JCI) and context-adapted models (NABH, CBAHI) demonstrated superior effectiveness compared to ISO standards alone, particularly when integrated with leadership engagement and organizational learning mechanisms. Conclusion This systematic review provides robust evidence that healthcare accreditation functions as a strategic enabler for patient safety and organizational excellence, with demonstrated improvements in safety outcomes, clinical practice adherence, leadership accountability, and quality culture. However, effectiveness is highly contextual, dependent on organizational readiness, sustained leadership commitment, and adequate resource allocation. The sustainability of benefits beyond reaccreditation cycles remains inconsistent and requires embedded systems for continuous monitoring and improvement. Significant disparities exist between high-income and low- and middle-income countries, necessitating tailored accreditation frameworks that balance standardization with contextual feasibility. Future research should prioritize longitudinal and controlled studies, standardized outcome measurement frameworks, comparative effectiveness analysis across accreditation models, and economic evaluations to optimize accreditation as a transformative mechanism for healthcare quality and safety globally. Keywords Healthcare accreditation; patient safety; quality improvement; organizational excellence; strategic enabler; hospital governance; clinical outcomes; safety culture; healthcare management; systematic review; PRISMA guidelines